The Effect Of Implementation Of Learning Method Of Team Based Learning On Motivation And Learning Outcomes Of Nursing Diploma Study Program In Health Academy Of Karya Husada Yogyakarta - Yunitasari, Pritta; kusumawati, Wiwik; afandi, Moh (Sekolah Tinggi Ilmu Kesehatan (STIKes) Karya Husada Semarang, 2016)
Learning motivation is an important thing owned by a Nursing student because it directly affects the student’s learning outcomes. The learning method of team based learning is student center learning strategy to improve the student’s motivation and learning outcomes. The research objective is to get to know the effect of implementation of learning method of team based learning on students’ motivation and learning outcomes compared to lecturing method. The research type is quantitative with quasi-experiment pre-test-post-test with control group approach. The research respondents are students of semester II in Nursing Diploma Study Program of Health Academy of Karya Husada Yogyakarta totaling 91 people. The research result shows that after getting intervension, the learning motivation of intervension group is higher than control group. The average value of intervension group is 119.19 ± 19.19, while control group is only 100.36 ± 23.26. The learning outcomes of intervension group is higher than control group. The average value of intervension group is 80.21 ± 11.58, while control group is only 60.46 ± 16.32. Therefore, it can be concluded that the improvement of motivation and learning outcomes of students of Nursing Diploma of Health Academy of Karya Husada Yogyakarta in the implementation of learning method of team based learning is higher than lecturing learning method.